ИСТРАЖУВАЊА НА НАРОДНАТА ДРАМА ВО МАКЕДОНИЈА – ИСТОРИСКА ПЕРСПЕКТИВА (Filološke studije, 2019)
Folkloristica as well as other scientific disciplines was formed in the nineteenth century. In that framework we need to look at its origins in the research of folk drama and theatre in the Macedonia. In the documents it remains remembered that the interest in this field of study of folklore in this region first appears by the end of the nineteenth century, when a large number collectors of folklore to start collect and write folk games and plays scene. True, more systematical research in the field of folk drama and theatre can be noticed after the Second World War In this paper it is desired to show the path of development on this part of the Macedonian, the study of folklore with special emphasis on the present situation, as well as on the work of some researchers who have produced a large contribution to define the field of its research and development.